محاسبـــــة التكاليـــــــــف كنظام للمعلومات واثرها في قرارات التسعيـــــــــــر: دراسة تطبيقية في الشركة العامة للزيوت النباتية (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Costs are considered the main factors in making pricing decisions in practical application for the availability of information related to these costs relatively to other factors in addition to the management direction toward covering costs in the long term , at least for the continuity of production .             Recently, the development occurred in the industry, the appearance of modern technology as a result of projects expansion and the use of automation in production that demands the increase of the activities for the purpose of productions engineering , and the concentration on examining and testing product before it is marketing , and the development of employees skills by using training courses curricula to improve their efficiency and skills in work . All these changes have great influence on increasing indirect costs , and at the same time decreasing the ratio of fee relatively to costs as a whole.